Case report: A novel WASHC5 variant altering mRNA splicing causes spastic paraplegia in a patient - Gao, Shan-Yu; Liu, Yu-Xing; Dong, Yi; Fan, Liang-Liang; Ding, Qi; Liu, Lv (Frontiers in Genetics, 2023)
Background: Hereditary spastic paraplegia (HSP) is a progressive upper-motor neurodegenerative disease. Mutations in WASHC5 gene are associated with autosomal dominant HSP, spastic paraplegia 8 (SPG8). However, due to the small number of reported cases, the exact mechanism remains unclear.We report a Chinese family with HSP. The proband was referred to our hospital due to restless leg syndrome and insomnia. The preliminary clinical diagnosis of the proband was spastic paraplegia. Whole-exome sequencing (WES) and RNA splicing analysis were conducted to evaluate the genetic cause of the disease in this family.Results: A novel splice altering variant (c.712-2A>G) in the WASHC5 gene was detected and further verified by RNA splicing analysis and Sanger sequencing.Real-time qPCR analysis showed that the expression of genes involved in the Wiskott-Aldrich syndrome protein and SCAR homologue (WASH) complex, endosomal and lysosome system were altered due to this variant.A novel heterozygous splice altering variant (c.712-2A>G) in the WASHC5 gene was detected in a Chinese family with HSP. Our study provided data for genetic counseling to this family and offered evidence that this splicing variant in the WASHC5 gene is significant in HSP.